A 21st Century Low‐Carbon Transition in U.S. Electric Power: Extent, Contributing Factors, and Implications. Issue 3 (13th June 2020) - Murray, Brian C.; Niver, William H.
Abstract: The U.S. electric power sector has experienced a substantial shift of the generation mix since the turn of the century, moving from heavy reliance on coal‐powered generation to one drawing more from natural gas and, more recently, renewables. This transition has been forged by a mix of macroeconomic factors (recession and recovery); technological breakthroughs (horizontal drilling coupled with hydraulic fracturing; improvements in natural gas plant efficiency); clean energy policies at federal, state, and local levels of government; and private sector demands for carbon‐free energy sources. These factors have combined to reduce carbon emissions from electric power generation substantially this century. In this article we examine the extent of this transition, its causes, as well as the distinct American institutional factors steering it, including energy and environmental federalism, electoral politics, and the political economy of clean energy policy enactment and resistance. Abstract : 美国电力部门自本世纪开始便经历了电力生产组合的实质性转变，从严重依赖燃煤发电转变到更多地使用天然气，以及近几年开始的可再生能源发电。宏观经济因素（经济衰退与恢复）、技术突破（水平钻井加上水力压裂、天然气厂效率提升）、联邦、州级和地方政府的清洁能源政策、以及私人部门对零碳能源的需求，这一切的组合共同形成了该能源转型。这些因素大幅减少了本世纪电力生产的碳排放。本文中我们检验了能源转型的程度、起因、以及引导该转型的独特美国制度因素，包括能源与环境联邦主义、选举政治、以及与清洁能源政策采纳与抵制相关的政治经济 Abstract : El sector de la energía eléctrica de EE. UU. Ha experimentado un cambio sustancial en la mezcla de generación desde el cambio de siglo, pasando de una gran dependencia de la generación a carbón a una que utiliza más gas natural y, más recientemente, energías renovables. Esta transición ha sido forjada por una combinación de factores macroeconómicos (recesión y recuperación), avances tecnológicos (perforación horizontal junto con fracturación hidráulica, mejoras en la eficiencia de la planta de gas natural), políticas de energía limpia a nivel de gobierno federal, estatal y local, y privado. demandas del sector de fuentes de energía libres de carbono. Estos factores se han combinado para reducir las emisiones de carbono de la generación de energía eléctrica sustancialmente este siglo. En este artículo examinamos el alcance de esta transición, sus causas, así como los distintos factores institucionales estadounidenses que la dirigen, incluido el federalismo energético y ambiental, la política electoral y la economía política de la promulgación y resistencia de políticas de energía limpia.